Tumor pyruvate kinase M2 modulators: a comprehensive account of activators and inhibitors as anticancer agents. Issue 7 (17th May 2021) - Rathod, Bhagyashri; Chak, Shivam; Patel, Sagarkumar; Shard, Amit
Abstract : The review focuses on the tumor pyruvate kinase M2 (PKM2) modulators. Both activators and inhibitors developed against PKM2 are discussed. Abstract : Pyruvate kinase M2 (PKM2) catalyzes the conversion of phosphoenolpyruvate (PEP) to pyruvate. It plays a central role in the metabolic reprogramming of cancer cells and is expressed in most human tumors. It is essential in indiscriminate proliferation, survival, and tackling apoptosis in cancer cells. This positions PKM2 as a hot target in cancer therapy. Despite its well-known structure and several reported modulators targeting PKM2 as activators or inhibitors, a comprehensive review focusing on such modulators is lacking. Herein we summarize modulators of PKM2, the assays used to detect their potential, the preferable tense (T) and relaxed (R) states in which the enzyme resides, lacunae in existing modulators, and several strategies that may lead to effective anticancer drug development targeting PKM2.